Manggrove Tourism Infrastructure and Recreation Facilities Development Planning - Simatupang, Rijal Ardiman (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2024)
The objectives of this thesis include: Identifying the application of the 6A concept (Attraction, amenities, accessibility, Available Package, Ancillary Service) and planning the development of infrastructure and recreation facilities for the mangrove tourism area in Tanjung Rejo village, Deli Serdang Regency, as well as formulating a design concept for the development of infrastructure and recreation facilities tourism in the mangrove area in Tanjung Rejo village, Deli Serdang Regency. To answer the first and second objectives, use Swot analysis using the 6A concept approach. The potential that Tanjung Rejo Village currently has includes: having a mangrove forest area which has become an icon of the village so that it is categorized as a pioneering ecotourism village, having natural resources which include flora and fauna which are used as a source of village income through innovative works using materials. nature as a dye for batik cloth and making some of the plants there into processed snacks that are suitable for sale, there is government support, organizations, namely forest farmer groups and tourism awareness groups which are collaborations between the village government and the community. There are three aspects of the benefits that Tanjung Rejo Village Mangrove Ecotourism has, namely social, economic and agribusiness aspects. as well as identifying the application of the 6A concept, a concept for planning the development of the Mangrove ecotourism area in Tanjung Rejo village was formulated, where this concept is one of the strengths for obtaining opportunities.